Substituent effects on fluoride binding by lanthanide complexes of DOTA-tetraamides - Blackburn, O; Routledge, J; Jennings, L; Rees, N; Kenwright, A; Beer, P; Faulkner, S (Royal Society of Chemistry, 2016)
Fluoride binding by a series of europium and ytterbium complexes of DOTA-tetraamide ligands derived from primary, secondary and tertiary amides has been studied by NMR and luminescence spectroscopies. In all the systems studied, fluoride binding results in a change in the nature of the magnetic anisotropy at the metal centre from an easy axis, to an easy plane anisotropy. This results in reversal of the peaks in the NMR spectra, and in changes to the fine structure of the luminescence spectra. Furthermore, changes to the periphery of the binding cavity are implicated in determining the affinity constant for fluoride. There are clear differences in the entropic contribution to the free energy of activation between systems with benzylic amides and those with methylamides.